On the influence of collinear surface waves on turbulence in smooth-bed open-channel flows. (10th October 2021) - Peruzzi, C.; Vettori, D.; Poggi, D.; Blondeaux, P.; Ridolfi, L.; Manes, C.
Abstract: Abstract : This work investigates how turbulence in open-channel flows is altered by the passage of surface waves by using experimental data collected with laboratory tests in a large-scale flume facility, wherein waves followed a current. Flow velocity data were measured with a laser Doppler anemometer and used to compute profiles of mean velocity and Reynolds stresses, and pre-multiplied spectra. The velocity signal containing contributions from the mean flow, wave motion and turbulence was decomposed using the empirical mode decomposition (EMD), which is considered a promising tool for the analysis of velocity time series measured in complex flows. A novel outer length scale h_0 is proposed which separates the flow into two regions depending on the competition between the vertical velocities associated with the wave motion and the turbulent velocities imposed by the current. This outer length scale allows for the identification of a genuine overlap layer and an insightful scaling of turbulent statistics in the current-dominated flow region (i.e. y/h_0 < 1 ). As the wave contribution to the vertical velocity increases, the pre-multiplied spectra reveal two intriguing features: (i) in the current-dominated flow region, the very large-scale motions (VLSMs) are progressively weakened but attached eddies are still present; and (ii) in the wave-dominated flow region (i.e. y/h_0 > 1 ), a new spectral signature associated with long turbulent structures (approximately 6 and 25 times the flow depth h ) appears. These longitudinal structures present in the wave-dominated flow region seem to share many features with Langumir-type cells.